Fluorine-18 chemistry in micro-reactors - LU, SHUIYU (2010)
Recent applications of micro-reactor (microfluidics) technology to radiofluorination chemistry within our laboratory are presented, based on use of either a simple T-shaped glass micro-reactor or a more advanced microfluidics instrument. The topics include reaction optimization and radioligand production, in particular the study of the radiofluorination of diaryliodonium salts, [(18)F]fluoride ion exchange with xenon difluoride(,) esterification with [(18)F]2-fluoroethyl tosylate, and the syntheses of [(18)F]fallypride, [(18)F]FBR and [(18)F]SL702 from [(18)F]fluoride ion.